Sekilas Tentang Perkembangan Pertunjukan wayang kulit di jawa dari masa ke masa Sebuah tinjauan historis - Sarwanto Sarwanto (Institut Seni Indonesia Surakarta, 2007)
The article discusses about the life and development of puppet show from time to time since 1920s until 1990s. PuppetÂ show, nowdays, has become more sophisticated and professional and it can become a guarantee that puppet show will continuously develop and will be able to compete with over popular art shows. Besides, the dalang with their developing creativities are able to work on tke pakeliran elements which can touch the aesthetic feeling and the audience interest. For the reason, the function of puppetÂ show as a guadiance as well as entertaining can be obtained.Â Key words: puppet show, lif and development, historical.